Pengaruh Kompensasi Terhadap Kinerja Karyawan pada PT. Sinar Galesong Mandiri Manado - Nelwan, Jerry; Pio, Riane J.; Rumawas, Wehelmina (JURNAL ADMINISTRASI BISNIS (JAB), 2019)
The purpose of this study is the purpose of this research is to find out and obtain a review of the effect of compensation on employee performance at PT. Sinar Galesong Mandiri Manado. The benefits of this research are expected that the results of this study can contribute to a broader knowledge of company performance and to be used as reference materials or comparison materials for other researchers. This is a quantitative descriptive study with a sample of 35 respondents obtained using the non-probability (accidental sampling) method. To test how the influence of quality is used instruments, validity and reliability tests, while the data were analyzed using a simple linear regression method with the t test and the coefficient of determination (multiple correlations). Therefore H1 is accepted, which means that the independent variable (compensation) influences the dependent variable (employee performance), positively and strongly influences. The results of the determination coefficient show that the adjusted R square rate is 0.592 or 59.2% which means that the employee performance variance can be explained by compensation. While the remaining 40.8 can be explained by other variables outside the research variable.